Slovenian Political Journalism in the European Perspective - Splichal, Slavko (Javnost-The Public, 2009)
This article presents theoretical and methodological design of two research projects, whose results are discussed by several contributions in the 2009 supplement of Javnost-The Public. Political Communication Cultures in Western Europe (2006-2010) is an international project under the auspices of the European Science Foundation, whose objective to analyze the relationship between political elites and the media on the basis of survey data collected in nine western European countries: Austria, Denmark, Finland , France, Germany, Slovenia, Sweden, Switzerland, and Spain. The second project, Diversity and political orientation of the Slovenian daily newspapers 1990-2005, is aimed at identifi ying changes in content and design, and main characteristics in presentnig political aff airs in the Slovenian daily press by using methods of content analysis. Though methodologically heterogeneous, the two projects are similar in their focus on the processes of modern mediatised political communication, professional roles and strategies of its participants - journalists and politicians - and interest in strengthening a democratic political culture.